Desempenho de formulações experimentais de gasolina em motormonocilíndrico de ignição por centelha com injeção direta - Lucimar Venancio Amaral (2019)
Gasoline is the most present fuel in the world energy matrix. According to Brazilian National Petroleum, Natural Gas and Biofuels Agency - ANP, in 2040 will be reached oil peak demand (ODDONE, 2018). Thus, there is a constant need to associate research aimed at increasing efficiency and reducing the consumption of this fuels in spark ignition engines. Commercial gasolines could have hundred components whichinfluence, in different ways, the spark ignition engine performs. In this work seven different formulations were tested in a single cylinder GDI (Gasoline Direct Injection) research engine with direct injection and stoichiometric mixture, one of these commercial formulations classified as Premium gasoline. Samples were tested with the engine at full load and speed ranging from 4000 to 5500 rpm at 500 rpm intervals.All had their combustion limited by the Lower Detonation Limit (LDI) and the properties were obtained with the tests: Indicated Mean Effective Pressure (IMEP), Indicated Specific Fuel Consumption (ISFC), Mass Burn Fraction at 50% (MBF50), Fuel Conversion Efficiency (cc), Mass Burn Fraction at 10-90% (MBF10-90) and exhaust temperature. The gasoline classified as Premium presented the best centralization ofthe combustion process, although it did not show the best performance indices (specific fuel consumption and fuel conversion efficiency) and did not have the highest octane rating (RON). These results may be used to develop new commercial formulations and to select appropriate percentages of the hydrocarbons used. Therefore, they can contribute in the development of better performing gasolines.